2022
DOI: 10.24093/awej/vol13no4.35
|View full text |Cite
|
Sign up to set email alerts
|

TESL Undergraduates’ Perceptions: Utilizing Social Media to Elevate Speaking Skills

Abstract: Teaching English as a Second Language undergraduates are English teachers in training. Recently, a concern arose when it was found that these undergraduates in Indonesia perceived their speaking skills as the lowest in terms of their mastery. Many studies have been conducted on the use of social media. Still, there is a literature gap in using social media among TESL undergraduates in the Malaysian context. Thus, this study aimed to explore TESL undergraduates’ perceptions of their speaking skill mastery and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…YouTube is reported to increase students' confidence in English speaking, lower their anxiety to learn faster and help retain attention (Albahlal, 2019). Many researchers have reached similar conclusions regarding the effectiveness of YouTube videos in enhancing speaking skills (Donny & Adnan, 2022;Muslem, Sahardin, Heriansyah, Fata, Djalaluddin & Hankinson, 2022;Saed, Haider, Al-Salman & Hussein, 2021).…”
Section: Introductionmentioning
confidence: 76%
“…YouTube is reported to increase students' confidence in English speaking, lower their anxiety to learn faster and help retain attention (Albahlal, 2019). Many researchers have reached similar conclusions regarding the effectiveness of YouTube videos in enhancing speaking skills (Donny & Adnan, 2022;Muslem, Sahardin, Heriansyah, Fata, Djalaluddin & Hankinson, 2022;Saed, Haider, Al-Salman & Hussein, 2021).…”
Section: Introductionmentioning
confidence: 76%
“…fostering a sense of healthy competition and achievement (Donny & Adnan, 2022). Teamwork in an online environment can promote communication, enhance collaborative skills, and create a more dynamic learning setting (Adnan & Sayadi, 2021).…”
Section: Research Samplementioning
confidence: 99%
“…Last but not least, mental readiness levels among students in online learning. Educational supports such as providing training on basic digital literacy skills (Donny & Adnan, 2022), providing additional assistance in language proficiency (Adnan & Sayadi, 2021) and offering technical support are important to make sure that students with access to online English classes can effectively utilize the available resources and understand the content. By focusing on these crucial aspects, students not only have access to online English classes but also receive the necessary support to succeed in their language learning journey.…”
Section: Research Samplementioning
confidence: 99%
“…This study supported participants' opinions because similar issues were revealed in previous research (Hsieh, 2019). ESL students were aware they required to communicate in English during the activity, but their lack of proficiency prevented effective communication (Lin & Nooreiny, 2013;Yan 2020;Donny & Adnan, 2022). Not only that, Storch (2016) noted that students' lack of confidence in communicating in English causes them to be reserved during the writing activity.…”
Section: Research Question 2: What Are the Benefits And Limitations O...mentioning
confidence: 99%